High-resolution time-series data of biogeochemical and physical parameters in a mangrove tidal creek - Alex Cabral; Juliana Hayden; Bárbara Viana; Marcos de Almeida; Tiago Passos; Roberto Barcellos; Stefano Bonaglia; Vanessa Hatje; Isaac R Santos (PANGAEA, 2025)
Hourly variation of salinity, depth, current velocity, temperature, dissolved oxygen, carbon dioxide, methane, nitrous oxide, radon, pH, rainfall, and wind speed during a complete neap-to-spring tidal cycle in a mangrove tidal creek. Field observations were conducted in a mangrove creek draining to Camamu Bay in tropical Brazil. The mangrove tidal creek (13°53 extquotesingle48.8S 39°02 extquotesingle57.6W) is situated in a pristine island without anthropogenic disturbances nor upstream river inputs. The mangrove creek intertidal catchment (0.86 km2) covers 16% of the island area. A time series station was deployed in a vessel moored in the mouth of a mangrove tidal creek from 4-15th of December 2023 to capture neap to spring tidal cycles. Depth and current velocities were measured using an ADCP (Nortek ECO) deployed on the bottom of the creek. Calibrated salinity and temperature (Solinst Levelogger 5), dissolved oxygen (PME miniDOT) and pH (Onset HOBO pH logger) probes were attached to the vessel at 0.5 m depth. A submergible water pump was installed from the vessel at 0.5 m below the surface to continuously transport surface mangrove creek water into a RAD AQUA showerhead gas equilibrator. The headspace air was pumped to a Drierite® desiccant, then into an automated radon (222Rn) detector (RAD7, DURRIDGE), and finally through CO2/CH4 (LI-COR 7810) and N2O (LI-COR 7820) trace gas analyzers (LI-COR, Biosciences) connected in series in a closed air loop. The greenhouse gas analyzers produced high-precision measurements every second using optical feedback-cavity enhanced absorption spectroscopy (OF-CEAS). The radon analyzer (RAD7) uses high resolution alpha spectroscopy. Atmospheric data (wind speed and precipitation) were obtained from local meteorological stations (A401 and A410), operated by the Brazilian Institute of Meteorology (INMET, https://bdmep.inmet.gov.br/). All datasets were smoothed to 1 hour time steps to enable comparisons across all variables.